Does retail type matter? Consumer responses to channel integration in omni-channel retailing. (July 2022) - Lim, Xin-Jean; Cheah, Jun-Hwa; Dwivedi, Yogesh K.; Richard, James E.
Abstract: A critical issue faced by marketing practitioners today is orchestrating strategies that provide a smooth consumer experience in an omni-channel environment. The extant literature offers limited guidance on managing the consumer journey in an omni-channel environment across different retail types. Using the S–O-R framework as its basis, this study generates novel insights by examining how different types of retailers influence consumer perceptions of channel integration (CPCI) as well as consumer empowerment, trust, satisfaction, and patronage intention. Data from 736 consumers was collected using purposive sampling to target those who interact with retailers from high-end specialty stores, department stores, and hypermarkets. The data was then analysed using partial least squares structural equation modelling (PLS-SEM). We find that consumers from high-end specialty stores, hypermarkets, and department stores have different perceptions when patronising the omni-channel retail business. The implications of the study are discussed and suggestions for future research are presented. Highlights: Multi-dimensional customer perceptions towards omni-channel retailing are assessed. 736 respondents were collected via stratified random sampling. PLS-SEM was applied to provide both explanatory and comparison assessments. Optimizing the retail outlet characteristics is key to the omni-channel strategies. Effective online relationship management will likely drive patronage intention.